Biodegradable blends and films having nano-structural features - LEE JAEHONG; WANG JAMES H; WIDEMAN GREGORY (2014)
A thermoplastic polymer composition with a tertiary blend of a carbon dioxide-derived polymer, a thermoplastic cellulose derivative, and a thermoplastic compatibilizer is described. The composition can be melt-processed into flexible, thin films that have fine nano-scale structural features in both the cross-directional and machine-directional orientations, for use in various products. The films, which are made from relatively brittle materials, exhibit a greater degree of ductility, elongation capacity, and strength than the primary, original component materials as binary-blends from which the film is made.